2014
DOI: 10.1111/jace.12953
|View full text |Cite
|
Sign up to set email alerts
|

Phase Evolution of Ga2O3 Produced from Morphology‐Controllable α‐GaOOH Nanocrystals

Abstract: Fine powders of GaOOH nanocrystals are synthesized via a facile hydrolysis process through the solution–solution interface reactions of anhydrous GaCl3 and distilled water followed by subsequent solvothermal treatment at mild conditions. Well‐faceted α‐GaOOH hexagonal prism‐like nanorods are prepared through solvothermal treatment at 180°C with CTAB as the morphology controlling surfactant. Ga2O3 nanocrystals are fabricated via the pyrolysis of α‐GaOOH hexagonal prism‐like nanostructures at temperatures above … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…It can also be confirmed that α-GaOOH is completely transformed into α-Ga 2 O 3 after annealing at 370 °C for 4 h due to the disappearance of the vibration related to the OH bond in the transition process. The above phenomenon directly proves the dehydroxylation process of α-GaOOH to α-Ga 2 O 3 , as shown in the following reaction equation: 24 2GaOOH → Ga 2 O 3 + H 2 OXRD and FT-IR tests both reflect the coexistence of α-GaOOH and α-Ga 2 O 3 at a certain temperature. Studying this transition state will help the understanding of the transformation from α-GaOOH to α-Ga 2 O 3 .…”
Section: Resultssupporting
confidence: 57%
“…It can also be confirmed that α-GaOOH is completely transformed into α-Ga 2 O 3 after annealing at 370 °C for 4 h due to the disappearance of the vibration related to the OH bond in the transition process. The above phenomenon directly proves the dehydroxylation process of α-GaOOH to α-Ga 2 O 3 , as shown in the following reaction equation: 24 2GaOOH → Ga 2 O 3 + H 2 OXRD and FT-IR tests both reflect the coexistence of α-GaOOH and α-Ga 2 O 3 at a certain temperature. Studying this transition state will help the understanding of the transformation from α-GaOOH to α-Ga 2 O 3 .…”
Section: Resultssupporting
confidence: 57%
“…Various kinds of strategies have been proposed to improve separation and transfer efficiency of the photogenerated charges, among which fabrication of phase junctions is an effective approach. [9][10][11][12] The phase junctions in polymorph semiconductors, such as the anatase/rutile phase junction in TiO 2 [2,[13][14][15][16][17][18][19][20] and α/β phase junction in Ga 2 O 3 [21][22][23][24][25] have been widely investigated. This kind of phase junction constructed by the different phases of the same semiconductor has attracted much attention due to its simplicity, controllability and great photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…These results confirm that the crystalline phase transition from γ-Ga 2 O 3 to β-Ga 2 O 3 occurred within 1440 min at 400°C. As discussed in the Introduction, the calcination of GaOOH, α-Ga 2 O 3 , or γ-Ga 2 O 3 at 700°C or above in air produces β-Ga 2 O 3 particles, 8,13,14,[17][18][19]26,28,35,36 which is the most stable phase. The detailed mechanism of the phase transition from γ-Ga 2 O 3 to β-Ga 2 O 3 has been reported recently.…”
Section: Resultsmentioning
confidence: 99%
“…22,23 Due to the wide application prospect of β-Ga 2 O 3 , its synthesis in the form of nanoparticles, nanorods, and thinfilms has received intensive research attention. Thus, for the synthesis of β-Ga 2 O 3 nanoparticles, a number of liquid processes based on the sol-gel method, 8,12,19,24 hydrothermal synthesis, 14,25,26 solvothermal synthesis, 18,[27][28][29] sonochemical method, 30 and solution combustion 31 were proposed. In most cases, the liquid processes involve the preparation of intermediate products such as GaOOH and γ-Ga 2 O 3 nanoparticles, which are then converted to β-Ga 2 O 3 nanoparticles by calcination at a temperature of 700°C or higher in air.…”
Section: Introductionmentioning
confidence: 99%